"More more more" said the baby : 3 love stories - Williams, Vera B. (New York : Mulberry Books, 1996)
Three babies are caught up in the air and given loving attention by a father, grandmother, and mother.
"A Mulberry Paperback book.".
Caldecott Medal/Honor.
Elem. School Library Collection.
Wilson's Children.
Book Links (A.L.A.), April 1996.
Booklist, January 1998.
Keywords: Babies -- Fiction; Grandparent and child -- Fiction; Parent and child -- Fiction; Grandparent-grandchild relationship -- Fiction; Infants -- Fiction; Parent-child relationship -- Fiction